The porcine cervix : morphological changes and infiltration of immune cells during oestrus and dioestrus in the sow - Edström, Karin (SLU/Dept. of Anatomy, Physiology and Biochemistry (until 231231), 2009)
During the oestrous cycle, the porcine cervix undergoes marked macroscopic changes: at oestrus the cervix is firm, and after termination of oestrus it progressively softens. However, little is known about the parallel microscopic changes in the cervix. Therefore, the aim of this study was to examine the histological properties of the epithelium and subepithelial connective tissue of the uterine cervix during oestrus and dioestrus; the morphology of the epithelium and the infiltration of cells of the immune system were described. In addition, the proliferative activities of the epithelium and subepithelial connective tissues were investigated by use of an immunohistochemical method that identifies a nuclear protein (Ki-67) present in proliferating cells only. Six sows, three in oestrus and three in dioestrus, were used for this study.